Retrosigmoid-transmeatal en bloc removal of small to medium-sized acoustic neuromas - Colletti, V; Fiorino, F G (Otolaryngology-head and neck surgery, 1999)
One hundred three subjects with acoustic neuroma (AN) underwent surgery--involving a retrosigmoid-transmeatal approach--between January 1990 and December 1995. All the intracanalar tumors (n = 18) and 70 of the intra- and extracanalar neuromas with an extracanalar neuroma size less than 25 mm--a total of 88 patients--constituted the final study population. The first 48 patients were operated on with the use of classic procedures described in the literature, characterized by limited exposure of the internal auditory canal and removal of the tumor after debulking. Surgery in the next 40 subjects was conducted according to the technique of en bloc removal of the tumor. The main features of this technique are continuous direct recording of cochlear and facial-nerve action potentials, wide opening of the internal auditory canal with lateral extension to the fundus, and removal of the tumor following the capsular lining without debulking. Statistical analysis of the results of the en bloc removal, compared with the previously used debulking technique, showed improvement in postoperative outcome for both auditory and facial-nerve function.